Ultrasonic Gravitational Wave Detector and the Results of its Application - Chernobay, I. A. (European Journal of Applied Sciences, 2025)
A new physical phenomenon has been established: the influence of gravitational fields on propagating acoustic and ultrasonic waves. Based on this, a new promising gravitational wave detector has been developed and successfully tested. For this purpose, two independent measurement channels with acoustically transparent media were created, in which ultrasonic waves propagate in mutually opposite directions. By creating certain physical conditions, ultrasonic waves are brought into a state of test bodies, continuously suspended in acoustically transparent media. The created test bodies, in the form of ultrasonic waves, are subjected to the influence of gravitational waves during their propagation. Through differential measurement of the mutual oscillations of ultrasonic waves that have passed through acoustically transparent media in mutually opposite directions, gravitational waves are reliably detected directly. The developed ultrasonic detector allows for continuous observation of numerous gravitational waves not only from our Galaxy, but also from the Universe. Gravitational explosions of supernovae are practically continuously observed from various directions in space. Through narrow-band frequency filtering, gravitational signals from neutron star pulsars can be distinguished from among tens of millions. Gravitational signals of unknown nature are also observed. The detector allows selective listening to gravitational waves in the audible frequency range. The operation of the detector provides evidence of the enormous speed of gravitational wave propagation compared to the speed of light. The importance of the obtained results lies in their fundamental nature, due to the direct detection method underlying the detector’s operation. This creates competition and a serious alternative to expensive projects for creating gravitational observatories based on laser interferometric observation methods.